2021
DOI: 10.1177/09544100211001490
|View full text |Cite
|
Sign up to set email alerts
|

Burning rate augmentation in solid fuel ramjets by swirling inlet air stream

Abstract: The influence of the inlet swirling flow on the regression rate of the fuel in the combustion chamber of the solid fuel ramjet is investigated in this study using numerical simulations. The finite-volume solver of the compressible turbulent reacting flow is developed to study the flow field where the burning rate is computed using the conjugate heat transfer method for the solid fuel. The correlation is found for the maximum regression rate versus an imposed inlet swirl when the linear distribution of the circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…Different features of the developed numerical program have been validated by various experimental, numerical, and analytical data, and this code has been successfully utilized to study different turbulent reacting flows in the past years where more details can be found in references like. [20][21][22][23][24][25]…”
Section: Governing Equations and Numerical Proceduresmentioning
confidence: 99%
“…Different features of the developed numerical program have been validated by various experimental, numerical, and analytical data, and this code has been successfully utilized to study different turbulent reacting flows in the past years where more details can be found in references like. [20][21][22][23][24][25]…”
Section: Governing Equations and Numerical Proceduresmentioning
confidence: 99%
“…More details on the governing equations and numerical procedure are presented in Ref. [7][8]. This program has also been validated using some experimental data, and used satisfactorily to study different reacting flow fields which details can also be found in Ref.…”
Section: Governing Equations and Simulation Proceduresmentioning
confidence: 99%
“…Therefore, some ideas have been proposed to augment the fuel regression rate in the combustion chamber of the solid fuel ramjets and increase the engine thrust level to the limit of this propulsion system. It has been illustrated that imposing the inlet flow swirl by using a swirler can increase the solid fuel regression rate [6], and a correlation has been found for its behavior [7]. The other way is an engine spin that can augment the regression rate and improve the performance, which has been analyzed recently in both steady and transient situations [8].…”
Section: Introductionmentioning
confidence: 99%
“…20 More details on the equations, numerical algorithm, and validations have been presented in Ref. 1113, 1718, and 2122.…”
Section: Governing Equations and Numerical Proceduresmentioning
confidence: 99%
“…Tahsini 13 performed numerical studies on the effect of the ramjet's spin on the regression rate of the solid fuel and proposed a relation for steady state condition and also illustrated that the transientburning phenomenon may occur at unsteady operation when the rapid spin-accelerations are imposed. In recent years, Musa et al [14][15][16] and Tahsini 17 conducted some experimental and numerical studies on the enhancement of the regression rate by inlet swirl for performance improvement of the SFRJs.…”
Section: Introductionmentioning
confidence: 99%